Dataversameling in navorsing: Die vraelys, onderhoud en prikkellys - E.B. Welman (AOSIS, 1982)
Nursing research as a scientific method of inquiry, has come to play an increasingly important role in nursing. The research process is a complex one and consists of several steps. Data collection, as one of the steps of research, should proceed according to a pre-established plan in order to minimise confusion and mistakes. The questionnaire, interview and checklist are three methods commonly used to collect data during research. The design and composition of the questionnaire, interview and checklist is time-consuming and needs careful planning. These methods have several advantages and disadvantages but can be used most effectively in reaching the ultimate goal of improving nursing standards.